A new hyperchaotic complex system and its synchronization realization. (3rd February 2021) - Li, Zhengfeng; Zhang, Fangfang; Zhang, Xue; Zhao, Yang
Abstract: In this paper, we propose a new hyperchaotic complex system and systematically study its basic dynamic characteristics such as dissipation, Lyapunov exponent, attractor, parameter changes, and Poincar e ́ cross-section. The system is based on the complex Lorenz chaotic system, and the chaotic system has higher dimensionality and more parameters than complex Lorenz system. We provide a general method for constructing complex chaotic systems. We use the state linear feedback method to realize the synchronization control of the chaotic system as the driving system and the response system and simulate all of the systems by Simulink. The chaotic system and its synchronization simulation are simulated by Simulink to verify their hardware feasibility.